Chemical constituents, usage and pharmacological activity of Cassia alata - Fatmawati, Sri; Yuliana, Yuliana; Purnomo, Adi Setyo; Abu Bakar, Mohd Fadzelly (Cell Press, 2020)
Cassia alata or locally known as Ketepeng Cina (Indonesia) and Gelenggang (Malaysia) has been used as a traditional medicine to treat various diseases, especially skin diseases. In addition, C. alata has been reported to have potential anti allergic, anti inflammatory, antioxidant, anticancer, antidiabetic, and antifungal. Metabolite compounds that have been isolated from C. alata include flavones, flavonols, flavonoids glycosides, alatinon, alanonal and β-sitosterol-β-D-glucoside. The compounds have been isolated mainly from the leaves. Further identification is needed to discover the secondary metabolites from other parts of the plant such as seed, flower and bark which are reported to have potent antibacterial and antifungal activity. Therefore, this article highlights the secondary metabolites and biological activity of this plant which has been shown to have pharmacological properties against selected diseases.